Holmium Laser in Urology-A Review Article - Islam, MS; Rashid, H; Waheed, S; Rakib, MA; Ashif, CM (Bangladesh Journal of Urology, 2020)
Abstract not available Bangladesh Journal of Urology, Vol. 14, No. 2, July 2011 p.58-61